Biotic agents for the management of American Serpentine leaf miner, Liriomyza trifolii(Burh=gess)(Diptera:Agromyzidae) - Jyothi Sara Jacob (Department of Agricultural Entomology, College of Horticulture, 2014)
A study on “Biotic agents for the management of American serpentine leaf miner, Liriomyza trifolii (Burgess) (Diptera: Agromyzidae)” was carried out at the Department of Agricultural Entomology, College of Horticulture, K.A.U., Vellanikkara during 2011-2013 with the objectives of collection and identification of indigenous natural enemies and to assess the pathogenicity of the entomopathogens to explore the feasibility of utilizing them for its management. Surveys were conducted in the vegetable fields for the collection and identification of natural enemies associated with L. trifolii in three districts, namely, Thrissur, Ernakulam and Kottayam from January to March, 2011. The surveys revealed the occurrence of nine species of hymenopteran parasitoids. The per cent parasitism varied from 10.96 to 58.99 per cent among the crops surveyed. Three species of eulophids, namely, Cirrospilus acadius Narendran, C. brevicorpus Shafee & Rizvi and Aprostocetus sp. as well as the braconid, Toxares sp. are new reports for India. Among the parasitoids, Closterocerus spp. were the dominant group followed by Chrysonotomyia sp. All parasitoids were solitary, larval endoparasitoids except Toxares sp. which was larval-pupal in nature. One species each of small ants (Formicidae) and a dipteran fly (Dolichopodidae) were observed as predators on L. trifolii. In the study, no entomopathogens were observed from L. trifolii. Considering the level of pesticide consumption in vegetable crops that undermine the potential of insect parasitoids and also that no entomopathogens could be observed during the survey, it was decided to evaluate entomopathogenic nematodes (EPNs) as biocontrol agents against L. trifolii. Isolation of EPNs from 72 soil samples from Thrissur, Ernakulam and Kottayam districts yielded four isolates of Steinernema carpocapsae. Bioefficacy studies carried out on these four isolates along with Steinernema bicornutum and Heterorhabditis indica showed that S. carpocapsae Isolate - 1 had the lowest LC 50 , LC 90 and LT values indicating their higher effectiveness against the maggots of the pest. 50 Pot culture study conducted to compare the potential of S. carpocapsae Isolate - 1 with other treatments showed that azadirachtin 1 EC at 0.005% was the most effective causing 84.51 per cent mortality to the maggots of L. trifolii. This was followed by the foliar application of H. indica at 32 infective juveniles (IJs)/ maggot which caused 18.98 per cent mortality. Application of Beauveria bassiana at 1×10 7 spores/ ml was not effective. In the field evaluation, fipronil 5 SC at 0.002% was found to be the most effective treatment for controlling L. trifolii followed by azadirachtin 1 EC at 0.005%. Compatibility of the IJs of the S. carpocapsae Isolate - 1, S. bicornutum and H. indica was studied with ten commonly used insecticides in the laboratory by direct exposure method. Chlorantraniliprole 18.5 SC at 0.005% was found to be the most compatible insecticide with S. carpocapsae isolate - 1 causing only 0.17 per cent mortality to IJs at 72 hours after treatment (HAT). Quinalphos 25 EC at 0.05% and chlorpyriphos20 EC at 0.05% were highly incompatible, causing 96.17 and 92.87 per cent mortality of the nematodes. Dimethoate 30 EC at 0.04% was the most compatible insecticide with S. bicornutum and caused only 0.60 per cent mortality at 72 HAT and was followed by azadirachtin 1 EC at 0.005% with 0.78 per cent mortality to the IJs. Quinalphos 25 EC at 0.05% caused 99.93 per cent mortality at 72 HAT. Heterorhabditis indica was compatible with all insecticides except quinalphos 25 EC at 0.05% which was moderately toxic resulting in 39.6 per cent mortality. The virulence, pathogenicity and multiplication of the survived IJs were not affected by the insecticide treatments. Parasitoids and EPNs were observed as potential candidates for the management of L. trifolii. Hence future studies on the bio-ecology and mass production of dominant parasitoids and standardization of methods to improve the efficacy of EPNs are suggested for the successful control of L. trifolii in polyhouses as well as in the field.